(untitled) (International Journal of Physiotherapy, 2015)
Background: The prevalence of musculoskeletal disorders has increased markedly with promotion of industrial life. It is one of the causes of absenteeism of employees from their work and significantly affecting their quality of life. The prevalence is not known in profession such as security guards, whose occupation comprises of prolonged standing mainly. Methods: A cross sectional survey was administered to 100 security guards in Guru Gobind Singh Super Thermal plant, Ropar, Punjab, India, using a self-structured questionnaire. Results: 100 security guards included in the study were in the age group of 30-50 years. 58% of the guards were alcoholic while only 19% were smokers. Out of 100 respondents, 68% had complained of MSDs in different areas while 32% did not complain of any musculoskeletal discomfort. Out of 68 security guards who had MSDs, majority of the guards had back pain42.6% . Higher prevalence of MSDs, 97.1% (33/34) had been found in 46-50 years of age, followed by age group of 41-45 years where the prevalence was 76.2%(16/21).The most common risk factor in our study identified was opening the gate again and again (98.5%) which could be due to the nature of their duty. Most common used coping strategy (69.9%) was to change from standing to sitting position when MSDs aggravates. Conclusion: It can be concluded that there is significant (68%) prevalence of MSDs in security guards. Demographic variables such as age, smoking and alcohol consumption have been found out to be contributing risk factors.